2008
DOI: 10.1094/mpmi-21-11-1421
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nonhost Resistance of Arabidopsis to the Asian Soybean Rust

Abstract: Asian soybean rust (ASR), caused by Phakopsora pachyrhizi, is a devastating disease of soybean. We report the use of the nonhost plant Arabidopsis thaliana to identify the genetic basis of resistance to P. pachyrhizi. Upon attack by P. pachyrhizi, epidermal cells of wild-type Arabidopsis accumulated H2O2, which likely orchestrates the frequently observed epidermal cell death. However, even when epidermal cell death occurred, fungal hyphae grew on and infection was terminated at the mesophyll boundary. These ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 56 publications
(80 reference statements)
2
94
1
1
Order By: Relevance
“…We investigated for the first time the interaction between Arabidopsis and P. pachyrhizi in our lab and we started, therefore, with a detailed cytological analysis of the fungal infection process on wild-type Arabidopsis plants. Doing so, we observed that the fungus was not only able to penetrate epidermal cell walls but also grew further to the border of the mesopyll tissue where the infection process came to an end (Loehrer et al, 2008). Penetration of epidermal cells of nonhost plants was a known phenomenon for P. pachyrhizi (Hoppe and Koch, 1989).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…We investigated for the first time the interaction between Arabidopsis and P. pachyrhizi in our lab and we started, therefore, with a detailed cytological analysis of the fungal infection process on wild-type Arabidopsis plants. Doing so, we observed that the fungus was not only able to penetrate epidermal cell walls but also grew further to the border of the mesopyll tissue where the infection process came to an end (Loehrer et al, 2008). Penetration of epidermal cells of nonhost plants was a known phenomenon for P. pachyrhizi (Hoppe and Koch, 1989).…”
Section: Discussionmentioning
confidence: 87%
“…It must be concluded, therefore, that P. pachyrhizi did not attack plants like a blind battering ram but rather utilizing subtle methods to cause cell death which might contribute to successful infection by avoiding active defense reactions. Looking at Arabidopsis mutant plants with impaired penetration resistance, we observed that after the breakdown of this first line of defense P. pachyrhizi w a s a b l e t o g r o w intercellularly into the mesophyll tissue and build haustorium mother cells (Loehrer et al, 2008). However, the pathogen was not able to invade mesophyll cells and establish haustorium-like structures until diminishing of a second line of defense in Arabidopsis pen2-1pad4-1 double mutants.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations